Foliar sprays of citric acid and salicylic acid alter the pattern of root acquisition of some minerals in sweet basil (Ocimum basilicum L.) - Ghazijahani, Noushin; Hadavi, Ebrahim; Jeong, Byoung R. (Frontiers in Plant Science, 2014)
The effect of foliar application of two levels of citric acid (CA; 0 and 7 mM) and two levels of salicylic acid (SA; 0 and 1 mM) combined with two levels of nutrient solution strength (full strength and half strength) on mineral acquisition by sweet basil were investigated. The experiment was conducted in a randomized block design arrangement with three replications. SA alone reduced the plant height and thickened the stem. Plants supplied with a full strength solution had a ticker stem, produced more biomass, and showed higher values of Fv/Fm. Some changes in the uptake pattern of some nutrients, especially boron and sulfur, were noticed. Higher boron concentrations in leaves were in plants sprayed with a combination of 7 mM CA and 1 mM of SA. Applying combination of CA and SA was more effective than using them individually that suggests an effective synergism between them.